2016
DOI: 10.1007/s12298-015-0334-y
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated genetic transformation of commercially elite rice restorer line using nptII gene as a plant selection marker

Abstract: Transformation of commercially important indica cultivars remains challenging for the scientific community even though Agrobacterium-mediated transformation protocols for a few indica rice lines have been well established. We report successful transformation of a commercially important restorer line JK1044R of indica rice hybrid JKRH 401. While following existing protocol, we optimized several parameters for callusing, regeneration and genetic transformation of JK1044R. Calli generated from the rice scutellum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Hygromycin resistance is an effective selection marker in regenerating rice plants. An alternative selection marker such as G418/kanamycin resistance is required, however, when introducing another transgene or the CRISPR/Cas9 cassette into the existing hygromycin-resistant transgenic rice plants (Chakraborty et al 2016 ; Park et al 2016 ). In the 23 vectors suitable for rice transgenic experiments, 13 contain the HptII gene and 10 contain the NptII gene (Additional file 1 : Table S1, Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Hygromycin resistance is an effective selection marker in regenerating rice plants. An alternative selection marker such as G418/kanamycin resistance is required, however, when introducing another transgene or the CRISPR/Cas9 cassette into the existing hygromycin-resistant transgenic rice plants (Chakraborty et al 2016 ; Park et al 2016 ). In the 23 vectors suitable for rice transgenic experiments, 13 contain the HptII gene and 10 contain the NptII gene (Additional file 1 : Table S1, Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical data in this study showed that more than 90% of the transformed calli were evidently positive with GUS stain, and about 36.7% of the calli exhibited a deep blue staining intensity (scoring = XXX). Previous studies reported that transformation using different vector backbones such as the pPZP200 and pCAMBIA2201 produced less than 65% of GUS-positive transgenic rice calli [31,32]. This indicates that the newly constructed pMDC140-wwin2 vector in this study provides a higher transformation success rate and is able to express GUS consistently in the transformed calli.…”
Section: Discussionmentioning
confidence: 68%
“…A amplificação do fragmento do gene nptII, nas amostras de raízes correspondentes, sugeriram a integração do T-DNA no genoma da pimenta longa (Figura 3). O gene nptII é o gene marcador de seleção mais utilizado em transformação genética de plantas (BHATTACHARYYA et al, 2014CHAKRABORTY et al, 2016. Ele codifica a enzima neomicina fosfotransferase II (nptII), também chamada aminoglicosídeo 3'-fosfotransferase II, que atua transferindo o grupamento  fosfato do ATP para um grupo 3-hidroxil da porção amino-hexose dos antibióticos aminoglicosados, como a canamicina, a neomicina, a geneticina e a paromicina, que assim são detoxificados por fosforilação (NYABOGA et al, 2014).…”
Section: Resultsunclassified